Penerapan Strategi Cost Efficiency (Efisiensi Biaya) Pada PT Bank Muamalat Indonesia, Tbk. Tahun 2017 - Nidaul Izzah; Muhammad Zakaria Rachmawan (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2019)
This research discusses about the implementation of the cost efficiency strategy at PT Bank Muamalat Indonesia, Tbk. As for the phenomenon of the problem that the authors observe on the financial ratios report of PT Bank Muamalat Indonesia, Tbk., especially in the BOPO ratio (Operating Costs to Operating Income), it ranks fourth highest out of a total of 13 Islamic Commercial Banks in Indonesia. Based on the authors’ observation, it has implemented the cost efficiency strategy that is also carried out by banks in general. However, there are some obstacles that result in inefficient bank performance, so the BOPO ratio is still high. Therefore, PT Bank Muamalat Indonesia, Tbk. has made several solutions to overcome the obstacles faced